2017
DOI: 10.1172/jci90848
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl hydroxylase 2 inactivation enhances glycogen storage and promotes excessive neutrophilic responses

Abstract: Fully activated innate immune cells are required for effective responses to infection, but their prompt deactivation and removal are essential for limiting tissue damage. Here, we have identified a critical role for the prolyl hydroxylase enzyme Phd2 in maintaining the balance between appropriate, predominantly neutrophil-mediated pathogen clearance and resolution of the innate immune response. We demonstrate that myeloid-specific loss of Phd2 resulted in an exaggerated inflammatory response to Streptococcus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 44 publications
3
91
0
Order By: Relevance
“…Neutrophils regularly function in the low‐oxygen environment of an active inflammatory tissue, and their extended survival and adapted function in hypoxia is thought to impact both positively and negatively on the outcome of inflammation . Consistent with the results of others, we noted marked inhibition of spontaneous apoptosis and an extended period of viability in human neutrophils in hypoxic conditions. Inhibition of apoptosis correlated with overall decreased surface expression of PS, and a delayed rate of caspase‐3 activation in the total neutrophil population indicates a global response to the hypoxic environment, and is consistent with previous observations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Neutrophils regularly function in the low‐oxygen environment of an active inflammatory tissue, and their extended survival and adapted function in hypoxia is thought to impact both positively and negatively on the outcome of inflammation . Consistent with the results of others, we noted marked inhibition of spontaneous apoptosis and an extended period of viability in human neutrophils in hypoxic conditions. Inhibition of apoptosis correlated with overall decreased surface expression of PS, and a delayed rate of caspase‐3 activation in the total neutrophil population indicates a global response to the hypoxic environment, and is consistent with previous observations.…”
Section: Discussionsupporting
confidence: 91%
“…Neutrophils are well‐equipped to function under hypoxic conditions as they are almost completely dependent on glycolysis and contain few mitochondria . Hypoxic exposure results in further up‐regulation of glycolysis and sustained ATP production, mediated by the activation of HIF‐1 . A number of studies have indicated that the primary neutrophil functions of chemotaxis and phagocytosis are sustained in low O 2 conditions …”
Section: Introductionmentioning
confidence: 99%
“…In that study, myeloid-specific loss of HIF-P4H-2 in mice caused a glycolysis-dependent delay in inflammation resolution paralleled by enhanced neutrophil survival and augmented chemotaxis. Application of the HIF-P4H inhibitor molidustat also enhanced neutrophil function and delayed resolution of inflammation [61]. Hence, while the liver and kidney-specific lack of HIF-P4H-2 appear to be beneficial under conditions such as HFD or lactic acidosis, the latter study suggests that in myeloid cells it may aggravate inflammation.…”
Section: Hypoxia Hifs and Hif-p4hs In Nonalcoholic Fatty Liver Diseamentioning
confidence: 91%
“…Another report, although not in liver, links HIF-P4H-2 inactivation with regulation of glycolysis, glycogen storage and inflammation [61], the latter being a feature of NASH. In that study, myeloid-specific loss of HIF-P4H-2 in mice caused a glycolysis-dependent delay in inflammation resolution paralleled by enhanced neutrophil survival and augmented chemotaxis.…”
Section: Hypoxia Hifs and Hif-p4hs In Nonalcoholic Fatty Liver Diseamentioning
confidence: 97%
“…Furthermore, they demonstrated that increased glucose consumption is crucial for enhanced neutrophil survival as neutrophils enter hypoxia. Recently, Sadiku and colleagues showed that Streptococcus pneumoniae pneumonia in Phd2 −/− mice leads to exaggerated neutrophil influx into the alveolar space, with fewer cells undergoing apoptosis at 72 hours, compared to wildtype mice [84]. Neutrophils from Phd2 −/− mice also show enhanced chemotaxis in response to the chemokine KC (murine analog of human IL-8).…”
Section: Mechanisms Of Hif-1α Stabilization Activation and Degradatmentioning
confidence: 99%